2023
DOI: 10.1108/ijoa-02-2023-3636
|View full text |Cite
|
Sign up to set email alerts
|

Green HRM impact on environmental performance in higher education with mediating roles of management support and green culture

Raghad Al-Alawneh,
Mohammed Othman,
Ahmed Adnan Zaid

Abstract: Purpose This paper aims to investigate the direct relationship between green human resource management (GHRM) practices and environmental performance (EP) in Palestinian universities, as well as the mediating role of management support (MS) and green organisational culture (GOC) in this relationship. Design/methodology/approach A quantitative approach was used in this study. The data were collected from 351 employees working in Palestinian universities through a questionnaire and analysed using partial least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…The core principle of RBV highlights the contribution of inner organizational resources that are “valuable, rare, inimitable, non-substitutable (VRIN)” as the foundation for achieving exceptional performance (Ren et al , 2021: 962). In line with this, GHRM is regarded as an effective strategy for advancing ecological sustainability (Aftab et al , 2023) and is viewed as a key resource for the firm through which it can achieve a competitive advantage (Al-Alawneh et al , 2023). An underlying principle of GHRM is that it enhances the competitiveness of firms, for example, through streamlining production processes, innovating new products and services, fostering collaboration across functions and promoting organizational learning (Ren et al , 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The core principle of RBV highlights the contribution of inner organizational resources that are “valuable, rare, inimitable, non-substitutable (VRIN)” as the foundation for achieving exceptional performance (Ren et al , 2021: 962). In line with this, GHRM is regarded as an effective strategy for advancing ecological sustainability (Aftab et al , 2023) and is viewed as a key resource for the firm through which it can achieve a competitive advantage (Al-Alawneh et al , 2023). An underlying principle of GHRM is that it enhances the competitiveness of firms, for example, through streamlining production processes, innovating new products and services, fostering collaboration across functions and promoting organizational learning (Ren et al , 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Viewing CEE as a resource, Chang (2011) contends that possessing an ethical culture can represent a resource that is VRIN. By recognizing the factors that influence employee green behavior (CEE in this case), organizations can enhance GHRM practices that lead to positive ecological results (Al-Alawneh et al , 2023). Within the scope of the present investigation, we recognize GHRM and CEE as important organizational resources (Gabler et al , 2022; Ren et al , 2021) that constitute a potential source of competitive edge.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Organizational culture as one of the organizational factors determine the success or failure of management in the workplace. Many studies relate its effectiveness depends on particular organizational culture in which it operates (Al-Alawneh et al ., 2023; Bass, 1997; Erkutlu, 2011; Yukl et al. , 2020).…”
Section: Organizational Culture and How It Influences Student Academi...mentioning
confidence: 99%
“…The specific norms, values and expectations of workplace culture underpin both leadership behavior and followers' performance (Hofstede, 1980; Robbins et al ., 2006). Previous studies found these elements to be antecedents to preferred leader behaviors (Dorfman and House, 2004), as well as influencing the way leadership process is carried out and its effects regarded by subordinates (Al-Alawneh et al ., 2023; Ferreira and Hill, 2008).…”
Section: Organizational Culture and How It Influences Student Academi...mentioning
confidence: 99%
See 1 more Smart Citation